EFEKTIVITAS ANTIBAKTERI BUNGA KENANGA (Cananga odorata) DENGAN METODE KONVENSIONAL TERHADAP PERTUMBUHAN Staphylococcus aureus - Nida Dusturia; Siti Roudlotul Hikamah; Diah Sudiarti (JURNAL BIOSHELL, 2016)
Ylang flower (Cananga odorata) is a plant that contains essential oils, flavonoids and saponins that are useful as a natural antibacterial. In this research, ylang flower antibacterial content obtained from a squeezed and boiled method. Serial concentrations used were 12,5%, 25%, 50% and 100%. While tetracycline 12.5% as the positive control and sterile distilled water as a negative control. There are differences in the effectiveness of antibacterial ylang flower of a squeezed and boiled method, it is known from the formation of inhibition zone on the test medium with Rancangan Acak Lengkap (RAL) 3x repetition. One Way Test results on freshly obtained ylang flowers calculated F value of 4.953 with 0.011 significance value, Ylang flowers being in the stew is not obtained F count. So in this research note ylang flower juice is more effective against Staphylococcus aureus growth compared with a decoction of ylang-ylang flowers.Keywords : Juice, Ylang flower (Cananga odorata), Staphylococcus aureus, Stews